THE EFFECT OF AWARENESS, TAX KNOWLEDGE, FISCUS SERVICES ON MANDATORY COMPLIANCE TAX OF PERSONAL PERSON WITH TAX SOCIALIZATION AS A MODERATING VARIABLE AT KPP PRATAMA BINJAI - Fatiya Kamila Hanoum; Syafrida Hani; Irfan (SEAN Institute, 2022)
This study aims to examine and analyze the effect of awareness, taxation knowledge, and fiscus services on personal taxpayer compliance with taxation socialization as a moderating variable at KPP Pratama Binjai. The level of compliance of personal taxpayers at KPP Pratama Binjai experienced a very large decline in 2021, namely 11.90%. The research method used is the quantitative associative method, namely a research assessing the correlation between two or more variables. The results of the study indicate that taxpayer awareness, taxation knowledge and fiscus services all influence taxpayer compliance. Tax socialization moderates the effect of taxpayer awareness on taxpayer compliance, but tax socialization does not moderate the effect of taxation knowledge and fiscus services on taxpayer compliance. Therefore, it is suggested to the KPP Pratama Binjai to improve its tax services to taxpayers beyond the desired standard so that it will later be able to influence taxpayers to improve taxpayer compliance